STUDENTS’ PERCEPTION ON THE IMPLEMENTATION OF MOODLE WEB-BASED IN LEARNING GRAMMAR - Nur Sehang Thamrin; Aminah Suriaman; Maghfirah Maghfirah (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2019)
Students in tertiary educational level in Indonesia, particularly at a state university in Centra Sulawesi are required to write a scientific paper as one of the requirements to complete their study period. The government even requires them to publish it in the academic online journal. It means that students construct it in the English language which students consider that writing an English article is difficult. Students produce several grammatical mistakes in their writing. They thought that learning grammar is such a difficult lesson and learning instruction is not interesting as teachers rely on one main resource. Nowadays, based on the researchers' investigation that there are several constraints that make the teaching-learning grammar is not effective and interesting; lack of references, time and space. While students need time to practice the language. Moodle as a part of information technology tools contributes to the solution to that constraint. After experiencing the grammar teaching-learning instruction, most students respond positive view toward the implementation of Moodle in the grammar teaching-learning process. Overall, almost all students respond that online learning instruction is needed.